Fenomena Pernikahan Dini dan Tinjauannya Secara Ekonomi di Kecamatan Sepulu Kabupaten Bangkalan - Pranata, Rhodi; Fahrullah, Arasy (Jurnal Ekonomika dan Bisnis Islam, 2021)
This study aims to determine the factors that drive early marriage in the Sepulu District of Bangkalan Regency. The method used in this research is descriptive qualitative using field research. information and data sources in this study are people who do early marriage in the District of Sepulu, Bangkalan District. This research uses the source triangulation method. the results of this study indicate that the factors driving the early marriage that occurred in the District of Sepulu Bangkalan District are economic factors, educational factors, parental factors, and customs factors.